2016
DOI: 10.1172/jci.insight.86397
|View full text |Cite
|
Sign up to set email alerts
|

A wearable artificial kidney for patients with end-stage renal disease

Abstract: BACKGROUND Stationary hemodialysis machines hinder mobility and limit activities of daily life during dialysis treatments. New hemodialysis technologies are needed to improve patient autonomy and enhance quality of life. METHODS We conducted a FDA-approved human trial of a wearable artificial kidney, a miniaturized, wearable hemodialysis machine, based on dialysate-regenerating sorbent technology. We aimed to determine the efficacy of the wearable artificial kidney in achieving solute, electrolyte, and volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
120
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(131 citation statements)
references
References 56 publications
(43 reference statements)
0
120
0
1
Order By: Relevance
“…These studies demonstrated the WAK to be a safe alternative to conventional dialysis, with no observable side-effects [10,11]. This preclinical evidence paved the way for the first pilot study involving the use of the WAK in humans, which was published in 2007 [4]. The study involved eight patients ranging from 26-67 years of age.…”
Section: Clinical Trials Of the Wakmentioning
confidence: 91%
See 4 more Smart Citations
“…These studies demonstrated the WAK to be a safe alternative to conventional dialysis, with no observable side-effects [10,11]. This preclinical evidence paved the way for the first pilot study involving the use of the WAK in humans, which was published in 2007 [4]. The study involved eight patients ranging from 26-67 years of age.…”
Section: Clinical Trials Of the Wakmentioning
confidence: 91%
“…In this paper we will explore the mechanisms by which the WAK operates, as well as the evidence for its efficacy and feasibility in clinical practice. The WAK device worn around the waist [4] dialysate fluids, which are needed in conventional dialysis to sustain filtration. The WAK is primed with a limited volume of sterile dialysate fluid which is purified by cycling through a series of microporous membranes comprised of sorbent fluids [8].…”
Section: Mechanisms Facilitating the Function Of The Wakmentioning
confidence: 99%
See 3 more Smart Citations